2020
DOI: 10.1111/febs.15589
|View full text |Cite
|
Sign up to set email alerts
|

NET formation – mechanisms and how they relate to other cell death pathways

Abstract: Cell death is an integral part of both infectious and sterile inflammatory reactions. Many cell death pathways cause the dying cell to lyse, thereby amplifying inflammation. A special form of lytic cell death is the formation of neutrophil extracellular traps (NETs), large structures of chromatin and antimicrobial proteins, which are released by dying neutrophils to capture extracellular pathogens and limit the spread of infections. The molecular mechanisms of NET formation remain incompletely understood. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 135 publications
(173 reference statements)
0
48
0
Order By: Relevance
“…The situation is further complicated by the fact that NET formation can take place even in the absence of necrosis. In other words, the development of NETs in humans occurs independently without the signaling of RIPK3 and MLKL, and the process is therefore independent of necroptosis 11 , 12 . Nevertheless, NETosis is considered a critical process that helps eliminate disease-causing pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is further complicated by the fact that NET formation can take place even in the absence of necrosis. In other words, the development of NETs in humans occurs independently without the signaling of RIPK3 and MLKL, and the process is therefore independent of necroptosis 11 , 12 . Nevertheless, NETosis is considered a critical process that helps eliminate disease-causing pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Although ETs are widely studied, NETs are a complex phenomenon, and there are still questions to be elucidated about the mechanisms involved in their formation (origin of the DNA, programmed cell death, signaling pathways), their role in host defense, and the pathophysiology of some diseases [6]. Many studies have been carried out in recent years; however, factors, such as the origin of the neutrophils used in the experiments, the isolation methods, the culture media, and/or the cell reactivation may influence the results, making it difficult to compare the results and the outline of unified knowledge about NETs [54,55]. Despite variations in nomenclature and classification, the mechanisms can share pathways, resulting in the release of extracellular DNA [2,5,10,20,22,23,55].…”
Section: Neutrophilsmentioning
confidence: 99%
“…NETs can also be classified as NADPH (NOX)-dependent and NOX-independent according to ROS production, since the presence or absence of ROS produced by NADPH oxidase in the cytoplasm or mitochondria seems to influence their formation [3][4][5]22,23,54]. In the formation of NOX-dependent NETs, various stimuli (e.g., PMA, cholesterol crystals, fungi, bacteria) induce ROS production by NADPH oxidase [10,23,54,55].…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the coexistence of dead vs viable, two types of NET formation, remains controversial. Thus, a recent consensus review article published by tens of investigators in NET formation research field suggested using the term "NET formation" instead of NETosis to cover the phenomenon of DNA release from neutrophils with or without cell death (26,27). Here, we will mainly focus on the dead NETotic neutrophils that release their nuclear chromatin to form extracellular NETs.…”
Section: Introduction -Netosis and Extracellular Net Formationmentioning
confidence: 99%